Missionaries and the Development of Modern Medicine in Wenzhou - CHEN Fengsheng, (Journal of Research for Christianity in China (JRCC), 2025)
In the modern history of Christianity in China, Western missionaries introduced advanced Western concepts and technologies in education, medicine, and other fields alongside the propagation of the Christian faith. As missionaries came to Wenzhou to spread their beliefs, the city's medical field also began to develop. Over the 150-year journey since Christianity's introduction, missionaries from the China Inland Mission established Wenzhou's first Western-style hospital, attempting medical evangelism. Meanwhile, missionaries from the Methodist Church vigorously developed healthcare services, making outstanding contributions to the advancement of medical care in the Wenzhou region.